Research on the evaluation criteria for safety state of train operation based on the scaled model. (September 2021) - Tong, Fengzhuang; Gao, Liang; Miao, Shuaijie; Xin, Tao; Cai, Xiaopei; An, Bolun
Highlights: The similarity criterion of vehicle-track coupling dynamics system is proposed. The differences in the accuracy of different train safety evaluation criteria by the scaled vehicle-track model are investigated. The whole process of derailment (wheel jumping and wheel climbing) and the critical interface (derailment and non-derailment) are analyzed. The new method to assess the train safety through the scaled vehicle-track model is designed. Abstract: To accurately predict the train operation state through the test results of the scaled vehicle-track test platform, based on the similarity theory and vehicle-track coupling dynamics theory, the similarity criterion of vehicle-track coupling dynamics system was proposed, and the dynamics models of vehicle-track system in scaled and full scale were established. The running characteristics of wheels under the critical state of derailment were analyzed, and a dynamic evaluation criterion of relative wheel-rail displacement (DEC-RWRD) was proposed. The results show that based on the proposed similarity criterion, the predicted displacement responses of the scaled vehicle-track model is consistent with that of the full scale vehicle. The differences in the accuracy of different train safety evaluation criteria by the scaled vehicle-track model are investigated, and the accuracy of the evaluation can be improved by DEC-RWRD. The combination of DEC-RWRD and the existing train dynamic monitoring methods can realize the prediction and the evaluation of trains' operation safety by the scaled vehicle-track test platform. The results can provide theoretical support for the dynamic evaluation of the safety status of high-speed train operation under severe line conditions and the experimental study of the whole process of derailment.